Immobilisation Of Tio2 Powder Onto Glass Plates Via Dip-Coating Technique Using ENR-50/PVC Polymer Blend As Adhesives And Its Photocatalytic Application - Ngoh , Ying Shin (2010)
The objective of this work is to produce a reusable immobilised TiO2 on glass plate utilizing polymer blend as adhesives for the photocatalytic degradation of methylene blue (MB) in aqueous solution. TiO2 powder (99% anatase) was directly immobilised onto glass plates using epoxidised natural rubber (ENR-50)/ poly (vinyl) chloride (PVC) polymer blend as adhesives via simple dip-coating technique. The photocatalytic characterization of the immobilised TiO2 powder was assessed using MB in aqueous solution as the model pollutant under the irradiation of 45W fluorescent lamp.